Garlic (Allium sativum) and Amla (Emblica officinalis) Powder Addition in the Diet Affects Production Performance of White Leghorn Laying Hens - Aswal, Pooja; Kumar, Anil; Singh, Pankaj (Indian Journal of Animal Nutrition, 2017)
This study was carried out to investigate the effect of dietary supplementation of garlic (Allium sativum) and amla (Emblica officinalis) powder on egg production and egg quality in laying hens for 8 weeks (26-33 weeks of age). One hundred and twenty white leghorn layers (26 weeks of age) were divided randomly into 4 groups in a complete randomized design. Birds of control group were fed control diet while the layers of other groups were fed the control diet supplemented with amla powder (@ 5 g/kg or garlic powder (@ 2 g/kg or garlic and amla powder + garlic powder (@ 2.5 and 1 g/kg. Production performance was studied in 2 periods of 28 days each (26-29 wk and 30-33 wk). There was an increase (P